A Requirement Model for Online Dental Reservation System for University Health Center - Said, Mohamed Ahmed (2008)
The rapid growth with the using of the online services becomes more necessary in the various fields. With A Requirement Model for Online Dental Reservation System for university health center the student will be able to make their reservation for the dentist appointment by online, the proposed system save the time and the effort on the student to make their reservation. A Requirement Model for Online Dental Reservation System for university health center can be obtained easy way to access the inquire information about the dentist appointment. This research introduces an online dentist application which provides the student the new technology to simplify the reservation process and to manage the appointment schedule by the dentist officer.